Analysis of Sand Shoveler Work Posture Using the Key Indicator Method (KIM) at UD. Pasir Berlian - Alvi Khoiruni Ritonga; Cut Ita Erliana; A. Amri (Jurnal Serambi Engineering, 2026)
Sand shoveling activities at UD. Pasir Berlian are still performed manually using non-ergonomic working postures, such as bending, lifting, and repeatedly transferring sand over long working hours. These conditions increase the risk of developing Musculoskeletal Disorders (MSDs) among workers. This study aims to assess the level of work posture risk and propose ergonomic improvements to work facilities in order to reduce the risk of MSDs. The study involved four sand-shoveling workers at UD. Pasir Berlian, North Labuhanbatu Regency. The research employed the Key Indicator Method for Lifting, Holding, and Carrying (KIM-LHC) to evaluate work posture risk, the Nordic Body Map (NBM) questionnaire to identify musculoskeletal complaints, and anthropometric measurements as the basis for designing an ergonomic work facility. Data were collected through observation, interviews, documentation, and questionnaires. The results showed that all workers obtained a KIM-LHC score of 200, indicating a high-risk category that requires immediate ergonomic intervention. The NBM results revealed that the most common musculoskeletal complaints occurred in the upper back, lower back, shoulders, arms, wrists, and legs due to repetitive shoveling activities and prolonged bending postures. To address these issues, an ergonomic platform or sand storage container was designed based on workers' anthropometric data to promote a more neutral working posture, reduce repetitive bending and manual lifting, and ultimately minimize the risk of MSDs while improving workers' comfort, safety and productivity.